Role Conflicts Experienced by Male College Varsity Football Players - Goldman, Moses V.; Robinson, Daniel C. (My University, 1989)
The purpose of this study was to examine the extent to which male college football players experienced role conflict. The possible interrelationship between race, eligibility classification, and experienced conflict as measured by the seven interpretable conflict variables (competition, psychological pressure, time, demand pressure. family, race and sport improvement needs) also was studied. A 67-item questionnaire developed by the authors was completed by 72 football students (76% on full scholarship, 24% walk-on) at a large Midwestern University at the end of the 1986 season about the extent and source of experienced role conflict over time, plus 32 demographic items. The results were submitted to factor analysis. The variables were studied with ANOVA and MANOVA. In general for this sample it appeared that football players did not experience a great deal of role conflict. It is theorized that this may be due in part to the fact that student athletes who participated in football at this university were provided with many support services. An analysis of the data showed that factors related to competition, psychologicai pressure and time produced the greatest amount of conflict for football players. These findings suggest that black student athletes who attend predominantly white institutions may have a much more difficult time coping with the demands of sports and academics than white athletes. Increasing the number of black support staff personnel would seem logical. The results of this study imply that an increase in black coaches, university, and athletic staff personnel might assist in remediating the amount of conflict felt by black student athletes. It was found that athletes differed significantly only in terms of the factors time and competition. It was found that freshmen and sophomores (underclassmen) experienced more conflict in relation to time variables than juniors and seniors (upperclassmen).
Keywords: identity; football; race; demographics